The other pandemic : an AIDS memoir - Curlee, Lynn, 1947- (Charlesbridge Teen, 2023)
"Interwoven with photographs of the people lost, this memoir chronicles the AIDS pandemic from the late 1970s to the late 1990s, up until the death of the author's partner"--